Orientational and structural properties of ferroelectric liquid crystal with a broad temperature range in the SmC(*) phase by (13)C NMR, x-ray scattering and dielectric spectroscopy - Bubnov, Alexej; Domenici, Valentina; Hamplová, Věra; Kašpar, Miroslav; Veracini, Carlo Alberto; Glogarová, Milada (Journal of physics. Condensed matter, 2009)
Thermotropic liquid crystalline materials laterally substituted by a methyl group on the aromatic ring of the alkoxybenzoate unit far from the chiral centre exhibit a very broad temperature range in the ferroelectric smectic C* (SmC(*)) phase on cooling (including supercooling) with a very high spontaneous polarization (∼210 nC cm(-2)) and tilt angle (∼43°) at saturation. We are presenting a detailed study of the physical properties of a ferroelectric compound, representative of this category of liquid crystals, by means of solid state (13)C-NMR, small angle x-ray scattering, dielectric spectroscopy and optical methods of the tilted SmC(*). Values of the spontaneous tilt angle measured optically are compared to those determined from the x-ray data and discussed. In addition, the viscosity has been determined in the SmC(*) phase by different experimental methods. (13)C NMR data allowed us to get information about the degree of orientational order of the SmC(*) phase and revealed the complete unwinding of the helical axis at the magnetic field of 9.4 T. This result is discussed in the framework of recent publications on the effect of the magnetic field on the supra-molecular structure of the SmC(*) phase.